Decreased inhibitory control after partial sleep deprivation in individuals reporting binge eating: preliminary findings - Cerolini,Silvia; Ballesio,Andrea; Ferlazzo,Fabio; Lucidi,Fabio; Lombardo,Caterina (PeerJ, 2020)
Background Poor executive functions are associated with dysregulated eating and greater caloric intake in healthy samples. In parallel, findings suggested that sleep deprivation impairs executive functions. Methods We investigated whether partial sleep deprivation impairs executive functions in individuals reporting binge eating (BE, N = 14) and healthy controls (C, N = 13). Switch cost and backward inhibition were measured using the Task Switching Paradigm after a habitual night of sleep and after a night of partial sleep deprivation. Results Results showed a Night by Group interaction on the backward inhibition. The two groups differed in the habitual night, evidencing higher inhibitory control in BE compared to C. Additionally, after partial sleep deprivation, compared to the habitual night, backward inhibition decreased in BE group. This preliminary study was the first to explore the impact of sleep deprivation on executive functions in participants reporting binge eating and healthy controls, thus highlighting their potential role in influencing eating behavior.
Keywords: Sleep deprivation; Binge eating; Executive functions; Inhibitory control; Disordered eating; Sleep